-73-9x=9x+17

Simple and best practice solution for -73-9x=9x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -73-9x=9x+17 equation:


Simplifying
-73 + -9x = 9x + 17

Reorder the terms:
-73 + -9x = 17 + 9x

Solving
-73 + -9x = 17 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-73 + -9x + -9x = 17 + 9x + -9x

Combine like terms: -9x + -9x = -18x
-73 + -18x = 17 + 9x + -9x

Combine like terms: 9x + -9x = 0
-73 + -18x = 17 + 0
-73 + -18x = 17

Add '73' to each side of the equation.
-73 + 73 + -18x = 17 + 73

Combine like terms: -73 + 73 = 0
0 + -18x = 17 + 73
-18x = 17 + 73

Combine like terms: 17 + 73 = 90
-18x = 90

Divide each side by '-18'.
x = -5

Simplifying
x = -5

You can always share this solution

See similar equations:

| 10km-km+5km-9km+3km= | | 4x+31=13x-68 | | 91-5x=10x+16 | | 2+7m= | | 5+5g= | | 8x-25=55 | | 3BC+BC+2BC+10BC-5BC= | | 3n+6p= | | x-2x+4x-8x=8 | | 3(x+5)=90 | | 3(4x+5)=-45 | | 5+2m+1= | | 7+7p= | | 4(x-6)-4(x-8)=-10 | | 7=5(1x-4)+2 | | 7q+8r-6r= | | 0.6666666y+5y=70-y | | 5x+2y=18 | | 4a+9a+2+4a= | | 2x-3y=11 | | 18=2(1g+4)+3(2g-6) | | 9+16x^2-24x=0 | | -4+6t-6= | | x-y=4v | | 3x+24=y | | 2n+4n-4n= | | 6(3.5+1r)-1=7r-r | | 10BC+7BC= | | 4t+7t+tu+8t= | | x=27 | | 8+1+9t= | | 5k+3k-4k= | | 8+7d= | | 3+k+7k= | | 1+2t= | | 4s+st= | | 4d+6d-7d= | | 5(x+2)=3x+7 | | -212b=-424 | | 8h-2h+10h= | | 7s+2=5-3s | | 6p-p= | | 4r-1=7 | | 2z+3yz-6z+2yz+y-z-4y= | | 5r-3r+7r= | | 3k-3k+8k+8km= | | 4x+27=x-3 | | 10n+8p= | | 6t-3t= | | 6+2s+2(8s+8)= | | n+6n= | | 4+3x=x-6 | | 3(1+5x)+7= | | 2(-5a-6)= | | 7w+7w+6w+5+7w= | | 4s+6s+6s+7= | | -3c+14=-7 | | 2(3x+5)=5(2x-4)-4x | | 10-15+2x=30 | | 15x+3(2x-1)=10(2x-3) | | -7p+3p+-5p= | | 2x+10-15=30 | | 6v+1+8v-9+9+5v= | | x^2-2=6-2x | | h+9h= |

Equations solver categories